Position as Well as Velocity Dependence of Spasticity—Four-Dimensional Characterizations of Catch Angle - Wu, Yi-Ning; Park, Hyung-Soon; Chen, Jia-Jin; Ren, Yupeng; Roth, Elliot J.; Zhang, Li-Qun (Frontiers in Neurology, 2018)
We investigated the muscle alterations related to spasticity in stroke quantitatively using a portable manual spasticity evaluator. Methods: Quantitative neuro-mechanical evaluations under controlled passive elbow stretches in stroke survivors and healthy controls were performed in a research laboratory of a rehabilitation hospital. Twelve stroke survivors and nine healthy controls participated in the study. Spasticity and catch angle were evaluated at 90˚/s and 270˚/s with the velocities controlled through real-time audiovisual feedback. The elbow range of motion (ROM), stiffness and energy loss were determined at a slow velocity of 30˚/s. Four-dimensional measures including joint position, torque, velocity and torque change rate were analyzed jointly to determine the catch angle. Results: The catch angle was dependent on the stretch velocity and occurred significantly later with increasing velocity (p<0.001), indicating position dependence of spasticity. The higher resistance felt by the examiner at the higher velocity was also due to more extreme joint position (joint angle) since the spastic joint was moved significantly further to a stiffer elbow position with the higher velocity. Stroke survivors showed smaller ROM (p<0.001), higher stiffness (p<0.001), and larger energy loss (p=0.005). Compared to the controls, stroke survivors showed increased reflex excitability with higher reflex-mediated torque (p<0.001) and with higher velocities (p=0.02). Conclusion: Velocity dependence of spasticity is partially due to joint position dependence with the joint moved further (to a stiffer position where higher resistance was felt) at a higher velocity. The 4-dimensional characterization including the joint angle, velocity, torque, and torque change rate provides a systematic tool to characterize catch angle and spasticity quantitatively.